The Communication Objectives of Sport Sponsorships - George Angelopulo; Nina Overton (Communicare)
SPORT sponsorship is increasingly used as an organisational communication tool. Its effective use is generally diminished by a lack of coordination with greater organisational communication objectives. The alignment of the objectives of sport sponsorship with an organisation's greater communication objectives as a means of increasing sport sponsorship's effective use is dis- cussed. The validity of differentiating be- tween objectives of sport sponsorship for public relations and for marketing communication objectives was tested amongst a sample of South African sponsors, and a measuring instrument of sport sponsors communication objectives was developed.